Evaluación de MIP OES para la cuantificación de micronutrientes - Perez, Maria Micaela; Brunello, Daiana; Cora Jofre, Florencia; Kloster, Nanci Soledad; Savio, Marianela (Asociación Argentina de la Ciencia del Suelo, 2023)
EEA Anguil